LOW-COST BIOMECHANICAL SYSTEM FOR THE EVALUATION OF PARKINSON'S - AUCCAHUASI, WILVER (2024)
PARKINSON'S IS A DEGENERATIVE DISEASE THAT IS FUNDAMENTALLY REPRESENTED BY LOSING CONTROL IN THE MOVEMENT OF THE HANDS, IN THE PRESENT WORK, A SYSTEM IS DEVELOPED TO MEASURE THE MOVEMENT OF THE HANDS, CONSIDERING PRONATION IN THE OPENING AND CLOSING ACTIONS OF THE HANDS AND SUPINATION. THE PRESENT DESIGN CONSIDERS THE USE OF INERTIAL SENSORS, RESULTING IN A DEVICE THAT CAN RECORD AND ANALYZE THE SIGNALS OF INVOLUNTARY MOVEMENTS OF PEOPLE WITH PARKINSON'S, THUS BEING ABLE TO ASSESS THE DEGREE OF THIS DISEASE, THE PROPOSED METHODOLOGY CONSIDERS THE POSSIBILITY OF BE ABLE TO BE REPLICATED AND ESCALATED. © 2024, THE AUTHOR(S), UNDER EXCLUSIVE LICENCE TO SPRINGER NATURE SINGAPORE PTE LTD.